THE EFFECT OF TRAINING AND TEAMWORK ON JOB PERFORMANCE, WITH EMPLOYEE JOB SATISFACTION AS AN INTERVENING VARIABLE AT PLN UP3 NORTH MEDAN - Indra Sintanta Sembiring; Kiki Farida Ferine; Sri Rahayu (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to determine the effect of training and teamwork on work performance with job satisfaction as a mediating variable on employees of PT. PLN (Persero) UP3 North Medan. The problem in this study is motivated by the importance of human resources with high work performance to support the achievement of organizational targets, but in practice there is still a mismatch between training and teamwork with the level of employee satisfaction and work performance. The population in this study were all employees of PT. PLN (Persero) UP3 North Medan, totaling 144 people. Because the population is less than 200, the sampling technique used is a saturated sampling technique, where the entire population is used as a sample. The data analysis method uses Structural Equation Modeling-Partial Least Square (SEM-PLS) with the help of SmartPLS software. The results of the study show that: (1) training has a positive and significant effect on work performance, but does not have a significant effect on job satisfaction; (2) teamwork has a positive and significant effect on job satisfaction and work performance; (3) job satisfaction has a positive and significant effect on work performance; (4) Job satisfaction significantly mediates the influence of teamwork on work performance, but does not significantly mediate the relationship between training and work performance. This study concludes that teamwork is an important factor in increasing job satisfaction and performance, while the effectiveness of training needs to be reviewed so that it can provide a more optimal impact on job satisfaction.